1991
DOI: 10.1111/j.1469-7610.1991.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociometric Status: Its Stability and Validity Among Neglected, Rejected and Popular Children

Abstract: Although important distinctions among sociometrically rejected, neglected, and popular children have been reported in the literature, concerns have been raised about use of negative peer nominations in identifying these children. A revised procedure developed by Asher and Dodge [Developmental Psychology, 22, 444-449 (1986)] eliminates the need to obtain negative peer nominations. In the present study, the construct validity of this revised procedure was explored and its long-term stability examined over 6, 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
3
27
0
1
Order By: Relevance
“…Considering the well-established evidence that social difficulties are a core component of ASDs, [49][50][51] our findings also suggest that the social disability observed in the ADHD + CBCL-AT group may be more a reflection of underlying ATs than the presence of ADHD itself. The higher rates of mood, anxiety, disruptive, and substance use disorders, 52 and school failure, school dropout, and delinquent offenses 53 in ADHD + AT children is particularly worrisome.…”
Section: E618mentioning
confidence: 99%
“…Considering the well-established evidence that social difficulties are a core component of ASDs, [49][50][51] our findings also suggest that the social disability observed in the ADHD + CBCL-AT group may be more a reflection of underlying ATs than the presence of ADHD itself. The higher rates of mood, anxiety, disruptive, and substance use disorders, 52 and school failure, school dropout, and delinquent offenses 53 in ADHD + AT children is particularly worrisome.…”
Section: E618mentioning
confidence: 99%
“…Whilst 69% of rejected children remained rejected, only 29% of neglected children persisted in this category. Their findings are supported by Ollendick et al (1991) who found only 11 % of neglected children in the same category after 12 months. Whilst these studies suggest that stability is not high it has been argued that, even though there is a fair amount of movement between categories over time, children tend to remain perceived in broadly the same terms by their peers within a consistent social environment.…”
Section: The Reliability and Stability Of Sociometric Statusmentioning
confidence: 62%
“…A less perjorative method of assessing sociometric status has been developed in which peers rate one another on a Likert scale, rather than nominate disliked peers (Asher & Dodge, 1986;Ollendick, Greene, Francis & Baum, 1991). For example, on a "1" to "5" scale, children are asked to rate how much they like to "spend time with" or "work with" each person in the class.…”
Section: Peer Rating Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their review article conclude that in general the stability of peer status increases with children's age and decreases with the length of the test-retest interval. Finally, popular, rejected and average groups of children are more stable than the neglected and controversial groups, which are highly unstable (Ollendick, Greene, Francis & Baum 1991;Asher & Dodge, 1986;Newcomb & Bukowski, 1983). In conclusion, research of both short-term and longterm stability points in general to moderate stability for status groups at the most (see Table 1 for an overview of the literature).…”
Section: An Overview Of Research On Stabilitymentioning
confidence: 96%